2022
DOI: 10.3892/etm.2022.11562
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant apatinib plus tegafur/gimeracil/oteracil potassium (S‑1)/oxaliplatin chemotherapy vs. chemotherapy alone in patients with locally advanced gastric carcinoma

Abstract: The current study aimed to evaluate the efficacy and safety of neoadjuvant apatinib plus tegafur/gimeracil/oteracil potassium (S-1) plus oxaliplatin (SOX) chemotherapy in patients with locally advanced gastric carcinoma (LAGC). Therefore, patients with LAGC treated with neoadjuvant apatinib plus SOX chemotherapy (apatinib + SOX group; n=25) or SOX chemotherapy (SOX group; n=35) were enrolled in the present study. Subsequently, the objective response (ORR) and disease control rates (DCR), pathological response,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We searched 1594 studies from 7 databases.Of these studies, 826 duplicate studies were excluded and two reviewers independently assessed the remaining 768 studies to determine their eligibility.Next, a total of 752 studies were excluded due to the following reasons: no control group (286); insu cient data (98); full text unavailable (143); quality assessment exclusion (139); combined PD-1/PD-L1 ( 89).Finally, a total of 13 studies were included [17-29] [17][18][19][20][21][22][23][24][25][26][27][28][29] .The detailed literature search process is shown in Fig. 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We searched 1594 studies from 7 databases.Of these studies, 826 duplicate studies were excluded and two reviewers independently assessed the remaining 768 studies to determine their eligibility.Next, a total of 752 studies were excluded due to the following reasons: no control group (286); insu cient data (98); full text unavailable (143); quality assessment exclusion (139); combined PD-1/PD-L1 ( 89).Finally, a total of 13 studies were included [17-29] [17][18][19][20][21][22][23][24][25][26][27][28][29] .The detailed literature search process is shown in Fig. 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the rst and most comprehensive meta-analysis of apatinib combined with chemotherapy in the treatment of primary intermediate and advanced GC.We included 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] with a total of 1217 cases, all of which were assessed as high-quality studies.The results of this study showed that in terms of e cacy, the ORR, R0 resection rate, and DCR of the observation group were better than those of the control group and were statistically signi cant.In addition to clinical e cacy, we analyzed the adverse events caused by apatinib.Speci c adverse events include: hypertension, anemia,thrombocytopenia,leukopenia,and diarrhea.Hypertension, hand-foot syndrome, and diarrhea in the observation group were higher than those in the control group and were statistically signi cant, which is consistent with the study by Xinyang Liu et al [30] .However, there were no signi cant differences in other adverse events between the two groups.Taken together, apatinib combined with chemotherapy can improve the e cacy of patients with advanced GC and has good safety.GC is a highly aggressive malignant tumor.Most patients are diagnosed at an advanced stage and often show symptoms such as distant lymphatic metastasis and pelvic metastasis.For these patients, systemic chemotherapy is the main treatment option [31] .Depending on human epidermal growth factor receptor 2 status, various combination regimens of uoropyrimidine and platinum with/without trastuzumab are commonly used as rst-line chemotherapy [32] .During or after rst-line chemotherapy for advanced GC, the disease Progressive symptoms often develop rapidly with associated deterioration in performance status, making patients unsuitable for systemic therapy [33] .Ramucirumab as a single agent or in combination with paclitaxel (preferred) is a category 1 recommendation for second-line treatment [34] can signi cantly improve PFS and OS in GC patients after rst-line treatment, either as monotherapy (REGARD [35] ) or in combination with paclitaxel (RAINBOW [36] ) [37] .However, regardless of the effectiveness of any currently available chemotherapy Regardless of the positive impact, the prognosis for patients with advanced GC remains hopeless, with a median survival of only 7-10 months in most large studies [31] .In recent years, with the development and progress of medicine, molecular targeted drug therapy has become a hot spot in clinical research, providing a new way to treat GC.The study by Caiyun Nie et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations